The Association of Body Mass Index With Mortality Among Pulmonary Hypertension Patients: A Systematic Review and Meta-Analysis of Cohort Studies - Jiang, Chaoxin; Fang, Xiongde; Fu, Wenjin (Frontiers in Public Health, 2022)
Objective: To run a systematic review and meta-analysis of related studies on body mass index (BMI) and the risk of death among pulmonary hypertension (PH) patients, as well as, to shed light on the shape and strength of the dose-response association. Methods: Studies published up to Jun 2021 in scientific databases such as Scopus, and PubMed as well as Google Scholar were searched. Cohort studies that reported risk estimates for at least two categories of BMI or per certain increase in BMI in relation to mortality in PH patients were included. Summary relative risks were determined with random effects models. Non-linear relationship was discovered with dose-response analysis. Results: All in all, 15 cohort studies were selected. The number of participants was 127215 out of which 73999 were reported dead. The relative risks (RRs) of mortality for participants with highest BMI were 0.72 (95% confidence interval (CI), 0.57–0.90; I2=97.3%, n=9) in comparison with the reference category. The summary RR for mortality per a 5-unit increment in BMI was 0.83 (95% confidence interval 0.77 to 0.89; I2=75.6%, n=9) among PH patients. There was a non-linear dose-response relation between BMI and mortality in PH patients (Pnon-linearity <0.001), with the lowest risk being at BMI 32-38 kg/m2. Conclusion: higher BMI is related to decreased risk of mortality among PH patients and the lowest point of the curve was seen at BMI 32-38.